ANALISIS DAYA SAING PRODUK EKSPOR PROVINSI SUMATERA UTARA - Budi Ramanda Bustami; Paidi Hidayat (Ekonomi dan Keuangan, 2013)
ABSTRACT The purpose of this research are to determine the development of leading export products and to find out how big the competitiveness of export products superior in the province of North Sumatra. Export products studied were 10 northern Sumatran province of superior products based on the Standard International Trade Classification (SITC). The data used in this study is time series data from the years 2000-2010. Data analysis method used is the method of competitive analysis Revealed Comparative Advantage (RCA), Revealed Trade Comparative Advantage (RCTA) and Trade Specialization Index (ISP). The results showed that 10 North Sumatra province superior products with competitiveness different. While there are some excellent products are not competitive or have a weak competitive positions, northern Sumatran province remains to export the products superior.   Keywords: Export, Product Competitiveness